PENGARUH KEEFEKTIFAN PENGENDALIAN INTERNAL, ASIMETRI INFORMASI, DAN MORALITAS INDIVIDU TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI DENGAN PERILAKU TIDAK ETIS SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Satuan Kerja Perangkat Daerah Provinsi Riau) - Delima Suma Bestari; Nur Azlina; Julita ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to determine the influence of effectivity of internal control, information asymmetry, and individual morality towards the accounting fraud tendencies with unethical behavior as intervening variable. This research was conducted at SKPD Riau Province. The sample was 89 employee level officials Echelon III and Echelon IV. Methods of data collection in this study using a survey method with questionnaire instrument. Data analysis method used SEM with SmartPLS which include validity, reliability, path analysis and bootstrapping. The result showed that the variable information asymmetry and individual morality significantly influence the accounting fraud tendencies by the unethical behavior as an intervening variable. While the variable effectivity of internal control does not affect accounting fraud tendencies by the unethical behavior as an intervening variable. Value of R-Square indicates that the variables jointly effectivity of internal control, information asymmetry, and individual morality contribute to the dependent variable (affect the accounting fraud tendencies) of 72,74%, while the remaining 27,26% is explained by other variables outside the research model.Keywords : Effectivity, Asymmetry, Morality, Fraud, and Unethical